Statistical Sampling in Auditing - EL-ARABI , ABDUSSALAM (Dirasat in Economics and Business, 1981)
In every audit the accountant performs, he must make sufficient tests of the records to support his opinion on the fairness of the financial statements. The auditor must not test an excess number of items to form his opinion nor test too few transactions. He must find a median which will keep the cost reasonable for the client and yet will allow the auditor to test enough transactions to substantiate his opinion. In this paper, the advantages of statistical sampling methods will be discussed along with illustrations of the ways the auditor can use statistical testing methods.